Travel blogging as a modern innovative tool for the development of tourism and excursion activities - Prykhodko, Z.; Yavorska, V.; Urash, Yu.; Sokolovskiy, V. (Journal of Education, Health and Sport, 2025)
The article is devoted to the analysis of such a modern tool for promoting a tourism product and the overall development of tourism activities as travel blogging The article emphasizes the basic concepts and features of travel blogging. The article describes the world and Ukrainian experience of travel blogging development and leading travel bloggers who are becoming key players in digitalization and start-up projects in the field of tourism and hospitality.